A influência translinguística sintática da libras na produção textual do português escrito como segunda língua para surdos - BISPO, Daniela dos Santos (2024)
This research has as general objective to investigate the translinguistic influence of the syntactic order of Libras for the Portuguese Language. It is assumed that late contact with the Sign Language affects the cognitive system of the student, and that this will later interfere with the learning of the Portuguese Language. It was adopted as a theoretical contribution: Souza (2014), which treats the translinguistic influence as being "the possibility of identifying characteristics of the most proficient language - L1, in the use of a less proficient language" L2 "and Tables 1997) that defends bilingualism as a proposal of teaching by schools that aim to make two children accessible to the child in the school context, namely, in the case of the deaf child, Libras as the first language and the Portuguese language in written form as second language. The material used for data collection was composed of a comic book without a title, "Luluzinha, a caçadora". A total of 3 (three) deaf students aged 18 and 24 years enrolled in the 7th and 8th years of elementary school teaching in the city of ToméAçu, Pará, Brazil. Participants were asked to observe a sequence of images, and then reported the sequence in Pounds and later in Portuguese in written mode. The results showed that there was no translingual linguistic influence of L1, Libras, on the L2, the Portuguese Language, because the deaf people could not tell the story in Libras nor write the text written in Portuguese, but only loose words without the construction of a syntactic structure.